1991
DOI: 10.1099/0022-1317-72-4-949
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence and organization of genes in a 5{middle dot}5 kbp EcoRI fragment mapping in the short unique segment of Marek's disease virus (strain RB1B)

Abstract: The DNA sequence of a 5.5 kbp EcoRI fragment located in the short unique region (Us) of the 'highly oncogenic' strain RB1B of Marek's disease virus (MDV) was determined. The sequence contained six open reading frames (ORFs), four of which were homologous to proteins mapping in the Us region of herpes simplex virus type 1 (HSV-1). These include the homologues of HSV-1 protein kinase, glycoprotein D (gD), glycoprotein I (gI) and US2 which is of unknown function. The MDV ORFs had a marked bias for A or T in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…The US2 gene of HSV-2 is predicted to encode a 291-amino-acid protein with a molecular mass of 33 kDa (McGeoch et al, 1987), and homologues of the US2 protein are encoded by many alphaherpesviruses and unclassified herpesviruses of birds, including HSV-1 (McGeoch et al, 1985), pseudorabies virus (van Zijl et al, 1990), Marek's disease virus (MDV) (Ross et al, 1991 ;Sakaguchi et al, 1992 ;Brunovskis & Velicer, 1995), equine herpesvirus type 1 (EHV-1) (Telford et al, 1992) and type 4 (EHV-4) (Nagesha et al, 1993), herpesvirus of turkeys (HVT) (Zelnı! k et al, 1993), bovine herpesvirus type 1 (LeungTack et al, 1994) and infectious laryngotracheitis virus (ILT) (Wild et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The US2 gene of HSV-2 is predicted to encode a 291-amino-acid protein with a molecular mass of 33 kDa (McGeoch et al, 1987), and homologues of the US2 protein are encoded by many alphaherpesviruses and unclassified herpesviruses of birds, including HSV-1 (McGeoch et al, 1985), pseudorabies virus (van Zijl et al, 1990), Marek's disease virus (MDV) (Ross et al, 1991 ;Sakaguchi et al, 1992 ;Brunovskis & Velicer, 1995), equine herpesvirus type 1 (EHV-1) (Telford et al, 1992) and type 4 (EHV-4) (Nagesha et al, 1993), herpesvirus of turkeys (HVT) (Zelnı! k et al, 1993), bovine herpesvirus type 1 (LeungTack et al, 1994) and infectious laryngotracheitis virus (ILT) (Wild et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A search for amino acid similarities using FASTP showed that ORF3 of MDV Us (Ross et al, 1991) was more closely related to the protein kinase of alphaherpesviruses mapping in Us than to any other sequence in the PIR database. Moreover, the conserved sequences were located within the catalytic domain of protein kinase as defined by Hanks et al (1988).…”
Section: Resultsmentioning
confidence: 99%
“…In view of the recent report of McGeoch (1990) that alphaherpesvirus genes mapping in Us may have been generated by a process of gene duplication and independent evolution, we have examined our sequence data for possible relationships not only between the MDV glycoprotein genes and their mammalian herpesvirus counterparts, but have also searched for similarities between the MDV genes themselves. Although we were unable to demonstrate a relationship between MDV ORF4 and other 0000-9949 © 1991 SGM herpesvirus proteins using FASTP (Lipman & Pearson, 1985) in our previous study (Ross et al, 1991) we now report that ORF4 is probably the homologue of HSV-1 gG and that it is also related to MDV gD. We present here an analysis which shows that MDV and mammalian alphaherpesvirus glycoproteins in Us constitute a family of inter-related genes.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations